2021
DOI: 10.1111/jipb.13112
|View full text |Cite
|
Sign up to set email alerts
|

LjaFGD: Lonicera japonica functional genomics database

Abstract: Lonicera japonica Thunb., a traditional Chinese herb, has been used for treating human diseases for thousands of years. Recently, the genome of L. japonica has been decoded, providing valuable information for research into gene function. However, no comprehensive database for gene functional analysis and mining is available for L. japonica. We therefore constructed LjaFGD (www.gzybioinformatics.cn/LjaFGD and bioinformatics.cau.edu.cn/LjaFGD), a database for analyzing and comparing gene function in L. japonica.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…Knowledge of the mechanism underlying the accumulation of VOCs associated with floral scents remains limited. The decoded genome of L. japonica has provided valuable information for research into gene function and transcriptomic analysis ( Pu et al, 2020 ; Xiao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the mechanism underlying the accumulation of VOCs associated with floral scents remains limited. The decoded genome of L. japonica has provided valuable information for research into gene function and transcriptomic analysis ( Pu et al, 2020 ; Xiao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the PCC distribution result, we found that the correlation between most genes was not high, mainly concentrated in the middle part ( Figure 1C ), and with the increase or decrease of correlation, the number of gene pairs gradually decreased ( Figure 1C ). Biological networks are usually scale-free with low network density ( Khanin and Wit, 2006 ; Broido and Clauset, 2019 ; Xiao et al, 2021 ). For the positive co-expression network, we evaluated and set the threshold of PCC in 0.6–0.95 to calculate the scale-free model fit index (R 2 ) and network density respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Genes in a co-expression network have similar expression patterns, so we reasoned that they may be regulated by the same transcription factors. Our previous co-expression network and motif analysis discovered the biosynthesis pathways of chlorogenic acid and luteolin in L. japonica might be regulated by MYB, bHLH, WRKY ( Xiao et al, 2021 ). Here, gene co-expression network and motif analysis show transcription factors might participate in the regulation of glycyrrhizin biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations